Multiorgan proteomic analysis of infected animal models predict potential host factors for chikungunya virus - Dongdong Lin; Cong Tang; Junbin Wang; Yun Yang; Hao Yang; Yanan Zhou; Wenhai Yu; Bai Li; Qing Huang; Haixuan Wang; Ran An; Xiaoming Liang; et al. (MedComm)
Abstract Chikungunya virus (CHIKV) is a mosquito‐borne alphavirus that is primarily known for causing severe joint and muscle symptoms, but its pathological effects have extended beyond these tissues. In this study, we conducted a comprehensive proteomic analysis across various organs in rodent and nonhuman primate models to investigate CHIKV's impact on organs beyond joints and muscles and to identify key host factors involved in its pathogenesis. Our findings reveal significant species‐specific similarities and differences in immune responses and metabolic regulation, with proteins like Interferon‐Stimulated Gene 15 (ISG15) and Retinoic Acid‐Inducible Gene I (RIG‐I) playing crucial roles in the anti‐CHIKV defense. We observed upregulated and downregulated metabolic status in CHIKV‐infected rhesus monkeys and mice, respectively. Additionally, we identified host factors such as S100 Calcium‐Binding Protein A8/A9 (S100A8/A9), Voltage‐Dependent Anion Channel 1/2 (VDAC1/2), Complement Component 3 (C3), Apoptosis‐Inducing Factor Mitochondria‐Associated 1 (AIFM1), Endothelial Cell‐Specific Chemotaxis Regulator (ECSCR), and Kininogen 1 (KNG1) that may contribute to CHIKV‐induced inflammation and hemorrhage. These insights put emphases on the importance of understanding CHIKV's impact on organs beyond joints and muscles, providing potential therapeutic targets and enhancing our understanding of CHIKV pathogenesis. This research underscores the need for appropriate animal models in CHIKV studies and informs the development of targeted therapies to address its systemic effects.